An RGB color-tunable turn-on electrofluorochromic device and its potential for information encryption. Issue 81 (28th September 2017) - Wang, Xiaojun; Li, Wen; Li, Wanru; Gu, Chang; Zheng, Hongzhi; Wang, Yuyang; Zhang, Yu-Mo; Li, Minjie; Xiao-An Zhang, Sean
Abstract : RGB color-tunable electrofluorochromic devices with a turn-on mode were fabricated successfully and applied for the first time in encrypted information storage and display. Abstract : RGB color-tunable "turn-on" electrofluorochromic (EFC) devices with high color purity (457 nm for blue, 539 nm for green, and 641 nm for red), relatively quick response/fading speeds and remarkable fluorescence contrast ratios are successfully fabricated. They exhibit great potential for increasingly important multistage encrypted information storage and displays.